(untitled) (Research, Society and Development, 2020)
The transition phases of the athletic career have specific demands and needs. Thus, investigating the personal attributes that the athletes have, such as self-determined motivation, coping strategies and parental support they receive, is necessary to verify the management of stressful situations within the sports context, in order to guarantee the adhesion and continuity of the sports practice. This research aimed to investigate the personal attributes of soccer athletes at different stages of athletic development. The subjects were 120 field soccer athletes from a club of the First Division of the Brazilian Championship (13 to 20 years old). As instruments, The Sport Motivation Scale, The Athletic Coping Skills Inventory and The Parenting Styles Inventory were used to assess personal attributes. Motivation, Coping Skills and Parenting Styles were compared among three stages of the sports career: Experimentation, Specialization, and Investment, using Levene’s Test, ANOVA with Bonferroni post hoc and Kruskall-Wallis with Mann-Whitney U to compare between pairs. The results showed the group of athletes in Investment Stage had higher values of Self-determination, greater range of Coping Skills and perception of Parenting Support. Throughout the sports career stages, personal attributes tend to improve, with Coping Skills and Self-determination geared towards training and performance. In addition, parental support is important to maintain the sporting career until the Investment stage.